Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Kepemimpinan Transformasional, Kepuasan Kerja dan Kinerja Manajer (Studi di Bank Syari’ah Kota Malang) - supriyanto, Achmad sani (Universitas Brawijaya, Indonesia, 2012)
The study aims to: examine, test, and evaluate the influence of emotional quotient (EQ) andspiritual transformational leadership on job satisfaction, and performance. The study is conducted inshariah banks in Malang. The research sample is 65 shariah banking managers. Sample determinationconsiders satumted sampling while research data analysis uses PLS (Partial Least Square). The resultshows that: emotional quotient (EQ) significantly influences transformational leadership, emotional quotient(EQ) significantly influences job satisfaction, emotional quotient (EQ) significantly influences performance,spiritual quotient (SQ) significantly influence transformational leadership, spiritual quotient (SQ)significantly influences job satisfaction, spiritual quotient (SQ) significantly influences performance, transformationalleadership significantly influences job satisfaction, transformational leadership significantlyinfluences performance, and job satisfaction significantly influences performance.